1999
DOI: 10.1111/j.1574-6941.1999.tb00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of soybean Bradyrhizobium strains adapted to the Brazilian savannas

Abstract: Brazilian soils are originally free from soybean bradyrhizobia and the first inoculants were brought to the country in this century, but a search for adapted strains started immediately and still continues. A strain selection program was established at Embrapa based on the reisolation of strains after a long period of adaptation to the soils followed by a search for variant genotypes with higher N(2) fixation capacity and competitiveness. A second approach of this program consists of searching for variant colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 17 publications
0
38
0
3
Order By: Relevance
“…After some years of soybean cropping, a high percentage of strains belonging to unknown serogroups or showing highly dissimilar DNA profiles have been detected in Brazil (Santos et al 1999;Ferreira et al 2000;GalliTerasawa et al 2003;Hungria et al 2006;Batista et al 2006). For example, in the South Region, Ferreira et al (2000) reported that 38% of the strains belonged to unknown serogroups after 17 years of soybean cropping, and in the Cerrados that percentage was about 50% after some years of cropping (Galli-Terasawa et al 2003;Mendes et al 2004).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After some years of soybean cropping, a high percentage of strains belonging to unknown serogroups or showing highly dissimilar DNA profiles have been detected in Brazil (Santos et al 1999;Ferreira et al 2000;GalliTerasawa et al 2003;Hungria et al 2006;Batista et al 2006). For example, in the South Region, Ferreira et al (2000) reported that 38% of the strains belonged to unknown serogroups after 17 years of soybean cropping, and in the Cerrados that percentage was about 50% after some years of cropping (Galli-Terasawa et al 2003;Mendes et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…However, dispersal of inoculant strains did occur (Ferreira and Hungria 2002;Mendes et al 2004) and Andrade and Hungria (2002) demonstrated that viable cells on the soybean seed coat can be transported to new cropping areas. After introduction through inoculation and some years of adaptation to the soil conditions, a high level of diversity in morphological, physiological, genetic, and symbiotic properties has been reported especially under the stressful conditions of the Cerrados (Hungria et al , 1998Nishi et al 1996;Boddey and Hungria 1997;Santos et al 1999;Hungria and Vargas 2000;Galli-Terasawa et al 2003;Batista et al 2006). In the USA, Streeter (1994) has also noted substantial "genetic adjustment" during the period of adaptation, leading to wide genetic diversity in field populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Identification and selection of highly efficient, locally adapted strains, which have established in soil after introduction of the inoculated host plant, is therefore possible. This approach has been used successfully with other species (e.g., Santos et al 1999), but the chances for success may be limited where the host is highly specific in its Rhizobium requirements.…”
mentioning
confidence: 99%